Sosialisasi Kebersihan untuk Mencegah Penyakit Cacingan (Helminthiasis) pada Murid SD Negeri 012 Padang Tanggung, Kecamatan Pangean, Kabupaten Kuantan Singingi, Provinsi Riau - Didi Kurniawan; Arif Rahman Zen; Ayu Febriani; Desti Juwita Harefa; Legi Oktri; M. Martunus Rawanda; Nova Sutriani; Putri Anita Permatasari; Risky Pebrinaldi; Widya Raphita Lumbantoruan (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The community service activity carried the theme "Socialization of Hygiene to Prevent Worm Disease (Helminthiasis) to Students of SD Negeri 012 Padang Responsibility, Pangean District, Kuantan Singingi Regency, Riau Province, was carried out as an effort to improve the cleanliness and health of elementary school age children by familiarizing the principles of sanitation of oneself with a culture of proper and good hand washing using soap, eating healthy and nutritious food as well as a culture of not littering. The elementary school age period is a glorious period to familiarize the values ​​of clean and healthy living behavior as well as the potential as an agent of change to introduce healthy living habits both in the school, family and community environment in order to create quality human resources in the future.